Strategic development organisations and bureaucratic psyche: a need for creating participatory culture - Rishi, Parul (2007)
State supported socio-economic development has been a notable feature of many third world countries. The major investment goes in the nation building industrialisation, infrastructure development and development of human resources through specially created and funded strategic developmental organisations which assume the responsibility for the growth and development of the domain in which they function. They clearly have a developmental mission but have moderate to high resource dependence on government. So, in spite of the mission requiring participatory modes of operation, they are trapped in the bureaucratic jungle loosing their real spirit and identity. They may be a weapon against poverty, inequity and backwardness but their functional effectiveness is dependent on their ability to tackle bureaucratic red tapism and, at the same time, obtaining the required resources from the government machinery. Based on this background, the article attempts to analyse the psyche of Indian administrators and reasoning for their resistance to adopt Participative Approach for the effectiveness of strategic developmental organisations. It is suggested that there is a need to fill the gap between Indian bureaucratic psychology and Participative Management Approach. Only then the intended results in the form of high individual, organisational and social effectiveness can be obtained for the successful functioning of strategic developmental organisations. - Reproduced.
Keywords: Strategic planning